$$\newcommand{C}[0]{\mathbb{C}}
\newcommand{div}[0]{\mathrm{div}}
\newcommand{division}[0]{÷}
\newcommand{grad}[0]{\mathrm{grad}\ }
\newcommand{N}[0]{\mathbb{N}}
\newcommand{Q}[0]{\mathbb{Q}}
\newcommand{R}[0]{\mathbb{R}}
\newcommand{rot}[0]{\mathrm{rot}\ }
\newcommand{Z}[0]{\mathbb{Z}}
$$
@infseriesbot
さんがツイートした
こちらの定理
の解説です.
以下の等式が成り立ちます.ただし$s\in\C_{\neq0}$とします.
$\displaystyle\int_0^\infty\frac{\sin sx}{e^{2\pi x}-1}\mathrm{d}x=\frac{1}{2}\left(\frac{1}{1-e^{-s}}-\frac{1}{s}-\frac{1}{2}\right)$
解説
\begin{align*}
&\int_0^\infty\frac{\sin sx}{e^{2\pi x}-1}\mathrm{d}x\\
=&\int_0^\infty\sin sx\frac{e^{-2\pi x}}{1-e^{-2\pi x}}\mathrm{d}x\\
=&\int_0^\infty\sin sx\sum_{k=1}^\infty e^{-2\pi kx}\mathrm{d}x\\
=&\int_0^\infty-\sum_{k=1}^\infty e^{-2\pi kx}\frac{\left(-s^2-\left(2\pi k\right)^2\right)\sin sx}{s^2+\left(2\pi k\right)^2}\mathrm{d}x\\
=&\int_0^\infty-\sum_{k=1}^\infty e^{-2\pi kx}\frac{-2\pi ks\cos sx-\left(2\pi k\right)^2\sin sx-s^2\sin sx+2\pi ks\cos sx}{s^2+\left(2\pi k\right)^2}\mathrm{d}x\\
=&\int_0^\infty-\sum_{k=1}^\infty\frac{-2\pi ke^{-2\pi kx}\left(s\cos sx+2\pi k\sin sx\right)+e^{-2\pi kx}\left(-s^2\sin sx+2\pi ks\cos sx\right)}{s^2+\left(2\pi k\right)^2}\mathrm{d}x\\
=&\int_0^\infty-\sum_{k=1}^\infty\frac{\left(\frac{\mathrm{d}}{\mathrm{d}x}e^{-2\pi kx}\right)\left(s\cos sx+2\pi k\sin sx\right)+e^{-2\pi kx}\left(s\left(\frac{\mathrm{d}}{\mathrm{d}x}\cos sx\right)+2\pi k\left(\frac{\mathrm{d}}{\mathrm{d}x}\sin sx\right)\right)}{s^2+\left(2\pi k\right)^2}\mathrm{d}x\\
=&\left[-\sum_{k=1}^\infty\frac{e^{-2\pi kx}\left(s\cos sx+2\pi k\sin sx\right)}{s^2+\left(2\pi k\right)^2}\right]_{x=0}^\infty\\
=&\sum_{k=1}^\infty\frac{s}{s^2+\left(2\pi k\right)^2}\\
=&\frac{i}{4\pi}\sum_{k=1}^\infty\frac{2\frac{is}{2\pi}}{\left(\frac{is}{2\pi}\right)^2-k^2}\\
=&\frac{i}{4\pi}\left(\pi\cot\pi\frac{is}{2\pi}-\frac{1}{\frac{is}{2\pi}}\right)\\
=&\frac{i}{4\pi}\left(i\pi\frac{e^{-\frac{s}{2}}+e^{\frac{s}{2}}}{e^{-\frac{s}{2}}-e^{\frac{s}{2}}}-\frac{2\pi}{is}\right)\\
=&\frac{1}{2}\left(-\frac{1}{2}\frac{e^{-s}+1}{e^{-s}-1}-\frac{1}{s}\right)\\
=&\frac{1}{2}\left(\frac{1}{2}\frac{2-\left(1-e^{-s}\right)}{1-e^{-s}}-\frac{1}{s}\right)\\
=&\frac{1}{2}\left(\frac{1}{1-e^{-s}}-\frac{1}{s}-\frac{1}{2}\right)
\end{align*}
なので,$\displaystyle\int_0^\infty\frac{\sin sx}{e^{2\pi x}-1}\mathrm{d}x=\frac{1}{2}\left(\frac{1}{1-e^{-s}}-\frac{1}{s}-\frac{1}{2}\right)$です.$\blacksquare$